2022
DOI: 10.1093/gji/ggac455
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variations in plume flux: characterizing pulsations from tilted plume conduits in a rheologically complex mantle

Abstract: Summary Along age-progressive hotspot volcano chains, the emplacement rate of igneous material varies through time. Time-series analysis of changing emplacement rates at a range of hotspots finds that these rates vary regularly at periods of a few to several tens of millions of years, indicative of changing melt production within underlying mantle plumes. Many hotspots exhibit at least one period between ∼2–10 Myr, consistent with several proposed mechanisms for changing near-surface plume flux,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…In this section we explore the possible mechanism of periodic swelling in the tail to produce multiple regular pulses. Earlier studies on flood basalt, hotspot swells, mantle plume evolution and melt migration in shallow mantle have shown that vertical fluid conduits embedded in another fluid can sustain nonlinear solitary waves (Olson and Christensen, 1986;Scott et al, 1986;Schubert et al, 1989, Helfrich andWhitehead, 1990;Neuharth and Mittelstaedt, 2023). Propagation of such waves causes the fluid conduit column to undergo alternate thickening and thinning, a phenomenon similar to pipe instability (Scott et al, 1986).…”
Section: Explanation For the Pulsating Plume Dynamicsmentioning
confidence: 98%
See 3 more Smart Citations
“…In this section we explore the possible mechanism of periodic swelling in the tail to produce multiple regular pulses. Earlier studies on flood basalt, hotspot swells, mantle plume evolution and melt migration in shallow mantle have shown that vertical fluid conduits embedded in another fluid can sustain nonlinear solitary waves (Olson and Christensen, 1986;Scott et al, 1986;Schubert et al, 1989, Helfrich andWhitehead, 1990;Neuharth and Mittelstaedt, 2023). Propagation of such waves causes the fluid conduit column to undergo alternate thickening and thinning, a phenomenon similar to pipe instability (Scott et al, 1986).…”
Section: Explanation For the Pulsating Plume Dynamicsmentioning
confidence: 98%
“…Schubert et al (1989) proposed a theoretical model to show the time scale of such pulses as a function of mantle viscosity. Their model predicts a time scale of 9 Ma for viscosity ~10 22 Pa S, which decreases to 1 Ma when the viscosity is ~10 21 Pa S. Recent computational simulations by Neuharth and Mittelstaedt (2023) have reported that the pulsating nature of plumes, caused by the destabilization of plume conduits, leads to periodic magmatic events.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While mantle composite rheology is typically considered in regional‐scale geodynamics models (e.g., Billen & Hirth, 2005; Garel et al., 2020; Neuharth & Mittelstaedt, 2023), it is often neglected in global‐scale models (e.g., Coltice et al., 2017; Li & Zhong, 2019; Stein et al., 2004), or simply mimicked by reduced activation energy in pure diffusion creep rheology (Christensen, 1983, 1984). However, this latter approximation causes differences in the planform of stagnant‐lid convection compared to using full composite rheology (e.g., Schulz et al., 2020).…”
Section: Introductionmentioning
confidence: 99%